Analisis Pengaruh Pajak Daerah, Retribusi Daerah, Dan Investasi Terhadap Produk Domestik Regional Bruto Dengan Belanja Modal Sebagai Pemoderasi - Della Siti Aisah; Andy Dwi Bayu Bawono (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to test the significant influence of regional taxes, regional levies and investment on gross regional domestic product with capital expenditure as a moderator. Using purposive sampling technique with a total sample of 191 districts/cities in Java. This research uses secondary data from the realization of the income budget. The analytical method used in the research is moderated regression analysis. The results of this research show that the Regional Tax and Regional Levy variables have a significant positive effect on Gross Regional Domestic Product, while the Investment variable has no significant effect on Gross Regional Domestic Product. Apart from that, the Capital Expenditure variable can moderate the Regional Tax and Regional Levy variables on Gross Regional Domestic Product so that it acts as a pure moderator, but the Capital Expenditure variable cannot moderate the Investment variable on Gross Regional Domestic Product because here it acts as a moderator homologizer. Keywords: Regional Tax, Regional Levy, Investment, Gross Regional Domestic Product, Capital Expenditure